Impact of the invasive alien plant species clearing programme on socio-economic benefits and plant biodiversity along the northern Drakensberg, Mpumalanga Province, South Africa - Bologo, Nthambeleni (University of the Free State, 2023)
The Working for Water (WfW) programme started in 1995, with the aim of controlling invasive alien plants in South Africa to protect a range of ecosystem services such as water and rangeland productivity, to protect biodiversity and create employment opportunities for previously disadvantaged rural communities targeting women, youths and people leaving with disabilities. The aim of this study was to investigate the effectiveness of the WfW programme focusing on three of their main objectives: (1) create sustainable jobs; (2) remove invasive alien plants from the river courses, grasslands, and indigenous forest; and (3) increase biodiversity. This study investigated the success of these objectives in the northern Drakensberg escarpment, Mpumalanga province, South Africa, by (1) determining the perceptions of employees and landowners on the impacts of the WfW programme through questionnaires, and (2) determining the impact of clearing on plant biodiversity through field surveys comparing plant diversity and cover-abundance in plots cleared by WfW and neighbouring uncleared grasslands. To determine whether the programme had created sustainable jobs, questionnaires were submitted to 80 community members who were employed in the WfW programme, in the study area, and 65 completed questionnaires. The surveyed family size ranged from one individual to eleven persons per household with an average of five people per household, and all had indicated that their primary source of income was from the WfW programme. The study found that most (46%) of the participants had a good knowledge of invasive alien plants (IAPs) while 86% of the respondents believe IAPs are a major problem, and 91% of the participants believed that WfW had benefitted communities living in the northern Drakensberg escarpment, with 97% indicating that the programme had improved their living conditions. This study further revealed that the programme has significantly contributed to rural communities’ livelihoods, but short-term contracts and intermittent funding have significant implications for the communities now relying on the funding. In addition, a limited number of landowners (10) were interviewed on their perceptions of the WfW programme. The findings revealed that most (60%) of the landowners who responded believed the programme was beneficial, and 70% of the landowners indicated that clearing of IAPs had increased stream flow and water availability. In addition, 90% of the landowners indicated that they had seen an estimated reduction of IAPs of between 20% to 80% on their properties due to clearing by WfW. Vegetation surveys were conducted at sites previously cleared by WfW teams (some as early as 1995) and paired with adjacent uncleared control sites. Initially, approximately 30 study sites were selected for investigation, which were refined to five suitable sites. The diversity and cover-abundance of plant species were surveyed in plots along transects within each pair of sites. Results showed that species diversity was significantly lower in cleared sites than in natural sites at Blyde river and Robbers Pass, while Graskop had significantly lower species diversity overall in both natural and cleared habitats. The NMDs plots showed that vegetation community assembly varied between cleared plots and open veldt across all sites, and more species were shared between sites in the Blyde river catchment and Pilgrims Rest. In addition, PERMANOVA results indicated that there were significant differences in plant communities between cleared and uncleared sites with lower species diversity in cleared plots. The study showed that despite areas being cleared for over ~25 years many important native species have not returned, and the communities remain different. Presumably, species recovery might not occur without some form of additional management, therefore restoration actions including monitoring of cleared sites should be considered to accelerate native vegetation recovery. In addition, landowner cooperation is critical to the success of WfW which seemed to be a challenge and needs to be strengthened to ensure improvement in the implementation of the programme. This study concludes that there is a need for quantitative, long-term, post management evaluations and assessments of the impacts of the funding models on communities used in broad scale initiatives. This will ensure that both the benefits and the failures of the project can be accurately determined to ensure its continued development and success. In addition, WfW should have dedicated funding for research to provide valuable long-term capacity. Finally, WfW should develop long-term clearing management plans with clear and realistic goals for all priority areas, and progress towards those should be routinely monitored to ensure continued improvement in the implementation of the programme.
Dissertation (M.Sc.(Botany))--University of the Free State, 2023
Keywords: Alien plants - Control; Invasive plants - Control; Working for Water (WfW) programme; Post management evaluation; Funding models; Community finance; Job creation - South Africa